A combined optical-thermal model for near-infrared laser heating of thermoplastic composites in an automated tape placement process. (August 2015) - Stokes-Griffin, C.M.; Compston, P.
Abstract: A combined optical-thermal model is presented for near-infrared laser heating of carbon fibre reinforced thermoplastic composites in an automated tape placement process. For the first time a three dimensional ray tracing model is presented for a near-infrared laser tape placement process which captures the unique anisotropic scattering behaviour of the composite. Predicted irradiance distributions on the composite are subsequently applied to a 2D non-linear finite element thermal model. It is shown that a shadow is present in the process and causes a significant drop in temperature prior to the consolidation zone. The effect of various source and surface model simplifications was also studied. The modelled temperature profiles agree well with experimental data. Substrate fibre orientation was investigated and found to have only a small influence on the temperature history.